Upf1p Control of Nonsense mRNA Translation Is Regulated by Nmd2p and Upf3p - Maderazo, Alan B. (American Society for Microbiology, 2000)
Upf1p, Nmd2p, and Upf3p regulate the degradation of yeast mRNAs that contain premature translation termination codons. These proteins also appear to regulate the fidelity of termination, allowing translational suppression in their absence. Here, we have devised a novel quantitative assay for translational suppression, based on a nonsense allele of the CAN1 gene (can1-100), and used it to determine the regulatory roles of the UPF/NMD gene products. Deletion of UPF1, NMD2, or UPF3 stabilized the can1-100 transcript and promoted can1-100 nonsense suppression. Changes in mRNA levels were not the basis of suppression, however, since deletion of DCP1 or XRN1 or high-copy-number can1-100 expression in wild-type cells caused an increase in mRNA abundance similar to that obtained in upf/nmd cells but did not result in comparable suppression. can1-100 suppression was highest in cells harboring a deletion of UPF1, and overexpression of UPF1 in cells with individual or multiple upf/nmd mutations lowered the level of nonsense suppression without affecting the abundance of the can1-100 mRNA. Our findings indicate that Nmd2p and Upf3p regulate Upf1p activity and that Upf1p plays a critical role in promoting termination fidelity that is independent of its role in regulating mRNA decay. Consistent with these relationships, Upf1p, Nmd2p, and Upf3p were shown to be present at 1,600, 160, and 80 molecules per cell, levels that underscored the importance of Upf1p but minimized the likelihood that these proteins were associated with all ribosomes or that they functioned as a stoichiometric complex.